Teachers’ creativity in applying English teaching methods - Titin Kaaba; Nurain Djalali (Journal of English Teaching and Linguistic Issues (JETLI), 2022)
The goal of this research is to determine creativity of teachers in applying English learning method. This research was carried out on 2 English teachers at SMP Negeri 1 Botumoito. A descriptive qualitative type was employed in this research with data collection techniques using semi-structured interviews. The results reveal that 2 English teachers who teach class 1 and class 2 at SMPN 1 Botumoito use various learning methods, those are: 1) discovery learning, 2) scientific learning, 3) question and answer/discussion, 4) project based learning, 5) roleplay, 6) demonstration, 7) and recitation method. From the implementation of all methods, teachers modify the stages according to learning materials, learning objectives and students’ needs. The combination of the above methods affects skills and enthusiasm of the students in responding to learning. Then, at evaluation stage the teachers apply various way including giving assignments to the students to see how active they are in asking and answering during the learning process.